PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT, EARNING PER SHARE, DAN RETURN ON EQUITY TERHADAP RETURN SAHAM - Yastami, Kadek Citra; Dewi, Putu Eka Dianita Marvilianti (Universitas Pendidikan Ganesha, 2022)
Stock return is the rate of return from investment activities undertaken. Many factors can affect the decline in the stock returns obtained. This study aims to determine and analyze the effect of sustainability report disclosure, earning per share, and return on equity to the stock returns of companies listed on KOMPAS100. This study method uses a quantitative approach. This study uses secondary data in the form of scientific journals, historical data on stock closing prices, annual financial reports, and sustainability reports. The population in this study were companies registered with KOMPAS100 during 2018 to 2020. The sample of this study was 16 companies which were obtained through purposive sampling technique. Data collection method in this study uses documentation method based on secondary data. Data analysis technique uses multiple linear analysis technique with SPSS application. The results of this study indicate that the sustainability report disclosure, earnings per share, and return on equity has a significant positive on stock returns.